FUTURE OF ALLOTMENT GARDENS IN THE CONTEXT OF CITY SPATIAL POLICY – A CASE STUDY OF POZNAŃ - Poniży, Lidia; Stachura, Kamila (Quaestiones Geographicae, 2017)
Multifunctional allotment gardens are an important part of the green infrastructure of cities. In spite of this, they are given little attention in the plans and policies of cities. One of the major threats to the existence of allotment gardens within the spatial structure of cities is the pressure of investment, which results from an underestimation of the role of gardens. The task of preserving allotment gardens in the ecosystems of cities rests with the local spatial planning. Urban spatial policy towards allotment gardening is exemplified by the case study of Poznan. The bases for the analysis include the study of the conditions and directions of spatial planning, as the spatial policy document that sets forth the city and local spatial development plans, which are Acts of local laws.